Fatty acid profiles of highly migratory resources from the Southeastern Pacific Ocean, Chile: a potential tool for biochemical and nutritional traceability - Fabián Guzmán-Rivas; Marco Quispe-Machaca; Jorge Lazo; Juan Carlos Ortega; Sergio Mora; Patricio Barría Martínez; Ángel Urzúa (PeerJ)
The traceability of fish species and their resulting food products is essential to maintain the global supply of these goods, allowing us to distinguish and reconstruct the origin and history of their production chain. One way to trace food is through biochemical determinations, which aid in identifying their geographical origin quickly. This study analyzed the fatty acid (FA) profiles of highly migratory fishery resource species (HMRS) from the Southeastern Pacific Ocean (SEPO), and their use as potential tools to determine the geographic origin and nutritional condition of these marine resources. The fatty acids (FAs) presented in fillet or muscle tissue of 18 HMRS were measured as FA methyl esters by gas chromatography. Our results reveal that the swordfish Xiphias gladius presented the greatest variety of FAs, strongly characterized by the presence of saturated, monounsaturated, and polyunsaturated FAs. A similar trend of high diversity in all classes of FAs was observed in tuna species (i.e., Thunnus alalunga; T. albacares; T. obesus), oilfish (Ruvettus pretiosus) and escolar fish (Lepidocybium flavobrunneum). In turn, Lampris guttatus, Makaira indica, and Tetrapturus audax presented an intermediate variety of FAs and the highest amount of saturated and monounsaturated FAs of the evaluated species. Finally, Luvarus imperialis, Coryphaena hippurus and the sharks (Lamna nasus; Alopias vulpinus; Prionace glauca; Isurus oxyrinchus; Sphyrna zygaena) presented a low diversity of FAs, with only saturated FAs strongly predominating. Regarding the total concentration of FAs, the highest average values were recorded in X. gladius, L. flavobrunneum and R. pretiosus. The present study revealed notable differences in the FA compositions of the muscle of diverse HMRS from the SEPO off the coast of Chile, with the swordfish showing the healthiest FAs (i.e., mono and polyunsaturated) for human consumption. The data on FAs collected for HMRS could be used as a reference to characterize the FA profiles of other fisheries in the SEPO (e.g., coastal pelagic fishes). In an ecosystem approach, our findings help us to understand how essential nutrients (i.e., FA biomolecules) are transferred through the marine food web in the SEPO, revealing the diet type and/or feeding habits of HMRS considered as top predators. Furthermore, identifying the FA profiles of fishery resources at a spatial level provides crucial information for their management and conservation, particularly in those resources that are overexploited and also have a critical nutritional importance for human consumption.